(untitled) (MAUSAM, 1978)
The present study was undertaken with a view to compute mean pattern of rainfall, upper winds and divergence field associated with monsoon depressions which had recurved and started moving northward. Mean charts were prepared by pooling together data of six such depressions using a moving co-ordinate system.